Spatial Filtering Versus Anchoring Accounts of Brightness/Lightness Perception in Staircase and Simultaneous Brightness/Lightness Contrast Stimuli - Blakeslee, Barbara (2009)
Cataliotti and Gilchrist (1995) reported that, consistent with anchoring theory, the lightness of a black step in a reflectance staircase was not altered by moving a white step from a remote to an adjacent location. Recently, Economou, Zdravkovic and Gilchrist (2007) reported data supporting three additional predictions of the anchoring model (Gilchrist et al., 1999): 1) equiluminant incremental targets in staircase simultaneous lightness contrast stimuli appeared equally light; 2) the simultaneous lightness contrast effect was due mainly to the lightening of the target on the black surround; and 3) the strength of lightness induction was greatest for darker targets. We investigated similar stimuli using brightness/lightness matching and found, contrary to these reports, that: 1) the relative position of the steps in a luminance staircase significantly influenced their brightness/lightness; 2) equiluminant incremental targets in staircase simultaneous brightness/lightness contrast stimuli did not all appear equally bright/light; 3) an asymmetry due to a greater brightening/lightening of the target on the black surround was not general; and 4) darker targets produced larger effects only when plotted on a log scale. In addition, the ODOG model (Blakeslee & McCourt, 1999) did an excellent job of accounting for brightness/lightness matching in these stimuli.